3D Printed Wesselsite Nanosheets Functionalized Scaffold Facilitates NIR‐II Photothermal Therapy and Vascularized Bone Regeneration. Issue 20 (15th August 2021) - Yang, Chen; Ma, Hongshi; Wang, Zhiyong; Younis, Muhammad Rizwan; Liu, Chunyang; Wu, Chengtie; Luo, Yongxiang; Huang, Peng
Abstract: Various bifunctional scaffolds have recently been developed to address the reconstruction of tumor‐initiated bone defects. Such scaffolds are usually composed of a near‐infrared (NIR) photothermal conversion agent and a conventional bone scaffold for photothermal therapy (PTT) and long‐term bone regeneration. However, the reported photothermal conversion agents are mainly restricted to the first biological window (NIR‐I) with intrinsic poor tissue penetration depth. Also, most of these agents are non‐bioactive materials, which induced potential systemic side toxicity after implantation. Herein, a NIR‐II photothermal conversion agent (Wesselsite [SrCuSi4 O10 ] nanosheets, SC NSs) with tremendous osteogenic and angiogenic bioactivity, is rationally integrated with polycaprolactone (PCL) via 3D printing. The as‐designed 3D composite scaffolds not only trigger osteosarcoma ablation through NIR‐II light generated extensive hyperthermia, but also promote in vitro cellular proliferation and osteogenic differentiation of rat bone marrow mesenchymal stem cells (rBMSCs) and human umbilical vein endothelial cells (HUVECs), respectively, and the ultimate enhancement of vascularized bone regeneration in vivo owing to the controlled and sustained release of bioactive ions (Sr, Cu, and Si). The authors' study provides a new avenue to prepare multifunctional bone scaffolds based on therapeutic bioceramics for repairing tumor‐induced bone defects. Abstract : An efficient multifunctional bone scaffold based on 3D printed SrCuSi4 O10 nanosheets/polycaprolactone composite is developed as SC/PCL, which possesses excellent therapeutic effects for deep‐seated osteosarcoma due to its high photothermal‐conversion efficiency in the second biological window. Moreover, the as‐designed 3D composite scaffold could facilitate the vascularized bone regeneration via the sustained release of bioactive ions (Sr, Si, and Cu).